Serum Creatine Kinase Concentration & Its Association with Severity in Acute Ischemic Stroke Patients: A Cross-Sectional Analytical Study (Bangladesh Journal of Neuroscience, 2016)
Background: The diagnosis of ischemic stroke remains a clinical one, with confirmatory evidence obtained through neuroimaging. Analogous to the role that the creatine kinase (CK), a biochemical test may be useful in diagnosis as well as detect severity which ultimately helps in the management of acute ischemic stroke.Objective: To evaluate serum creatine kinase level and its association with severity in acute ischemic stroke patients.Methods: This cross-sectional analytic study was carried out in the Department of Neurology, BSMMU, Dhaka from January 2014 to December 2014.In this study 50 acute ischemic stroke patients were enrolled as cases.Result: In this study, 42.0% patients were female and 58% were male and their mean age was 55.96±10.93 years. According to classification by NIH Stroke score, 32% patients was found in minor stroke, 28% in moderate stroke, 26% in moderate to severe stroke and 14% in severe stroke. 80.0% patients had increased level of serum creatine kinase. In this study there is a positive correlation between NIH Stroke Score and Serum creatine kinase level (r= 0.869, p < 0.0001).Conclusion: Increase severity of acute ischaemic stroke causes increased level of serum creatine kinase.Bangladesh Journal of Neuroscience 2016; Vol. 32 (2): 52-55